Enhanced Reactivity of Accessible Protons in Sodalite Cages of Faujasite Zeolite. (18th December 2021) - Li, Xinyu; Han, He; Xu, Wenqian; Hwang, Son‐Jong; Lu, Peng; Bhan, Aditya; Tsapatsis, Michael
Abstract: Faujasite (FAU) zeolites (with Si/Al ratio of ca. 1.7) undergo mild dealumination at moderate ion exchange conditions (0.01 to 0.6 M of NH4 NO3 solutions) resulting in protons circumscribed by sodalite cages becoming accessible for reaction without conspicuous changes to bulk crystallinity. The ratio of protons in sodalite cages (HSOD ) to supercages (HSUP ) can be systematically manipulated from 0 to ca. 1 by adjusting ammonium concentrations used in ion exchange. The fraction of accessible protons in the sodalite cages is assessed by virtue of infrared spectra for H‐D exchange of deuterated propane based on the band area ratio of OD2620 /OD2680 (ODSOD /ODSUP ). Protons in sodalite cages (HSOD ) show higher rate constants of propane dehydrogenation ( k D ) and cracking ( k C ) than protons in supercages (HSUP ) plausibly due to confinement effects being more prominent in smaller voids. Rate constants of dehydrogenation and cracking including k D / k C ratios are also augmented as the fraction of accessible protons in the sodalite cages is enhanced. These effects of accessibility and reactivity of protons in sodalite cages hitherto inconspicuous are revealed herein via methods that systematically increase accessibility of cations located in sodalite cages. Abstract : Faujasite (FAU) zeolites (with Si/Al ratio of ca. 1.7) undergo mild dealumination at moderate ion exchange conditions (0.01 to 0.6 M of NH4 NO3 solutions) resulting in protons circumscribed by sodalite cages becoming accessible for reaction. The ratio of protons in sodalite cages (HSOD ) to supercages (HSUP ) can be manipulated by adjusting ammonium concentrations used in ion exchange.